Inclusive STEM Learning for Enhancing Student Participation: A Bibliometric and Systematic Literature Review - Abdurrohman Khotim Nugraha; Chaerul Rochman; Dindin Nasrudin; Siti Rahaimah Binti Ali; Evi Muliyah; Sitti Maesuri Patahuddin (Jurnal Inovasi Pendidikan IPA, 2026)
The study aimed to analyze the thematic focus and review the literature on the implementation of inclusive STEM education to enhance student participation in learning, as well as to address four research questions of the STEM education system, inclusive teaching practices, the principles of diversity, equity, and inclusion (DEI), and access to quality education. The particular study integrated bibliometric analysis (BA) and a systematic literature review (SLR). Article metadata from Scopus was extracted on December 7, 2025, and rigorously selected using the PRISMA 2020 protocol. Applying specific inclusion and exclusion criteria to ensure the study’s relevance and depth yielded 52 core journal articles that published between 2021 and 2025. The analysis identified four thematic clusters: the STEM learning system, inclusive teaching, diversity, equity, and inclusion (DEI), and access to quality education. The synthesis indicates that students’ participation in inclusive STEM learning is shaped by a student-centered, contextual, flexible, and collaborative system design; inclusive pedagogy through differentiation, a safe classroom climate, and equitable formative assessment; the application of DEI principles; and support for access to quality education through institutional support and a transformation of the learning culture.